2004
DOI: 10.1021/ic0351592
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Characterization of Arsenite in Water:  Insights into the Coordination Environment of As−O

Abstract: Long-term exposure to arsenic in drinking water has been linked to cancer of the bladder, lungs, skin, kidney, nasal passages, liver, and prostate in humans. It is therefore important to understand the structural aspects of arsenic in water, as hydrated arsenic is most likely the initial form of the metalloid absorbed by cells. We present a detailed experimental and theoretical characterization of the coordination environment of hydrated arsenite. XANES analysis confirms As(III) is a stable redox form of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
84
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 129 publications
(95 citation statements)
references
References 12 publications
10
84
0
1
Order By: Relevance
“…However, studies have shown that arsenic in the form of arsenic trihydroxide (As(OH) 3 ), the water soluble form of arsenite, enters cells rapidly through human aquaglyceroporins (hAQP9 and hAQP7) (Liu et al, 2004). In addition, non-ionic arsenite transport appears to be involved in the cellular uptake process while ionic transport does not (Ramirez-Solis et al, 2004). We have shown that arsenite accumulates in A375 and SK-Mel-28 cells and that inhibition of arsenite detoxification and metabolism increases arsenic accumulation (McNeely et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies have shown that arsenic in the form of arsenic trihydroxide (As(OH) 3 ), the water soluble form of arsenite, enters cells rapidly through human aquaglyceroporins (hAQP9 and hAQP7) (Liu et al, 2004). In addition, non-ionic arsenite transport appears to be involved in the cellular uptake process while ionic transport does not (Ramirez-Solis et al, 2004). We have shown that arsenite accumulates in A375 and SK-Mel-28 cells and that inhibition of arsenite detoxification and metabolism increases arsenic accumulation (McNeely et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Every mole of ATO in solution is equivalent to 2 moles of sodium arsenite. The most stable structure of trivalent arsenic oxides existing in solution at neutral pH is As(OH) 3 (Ramirez-Solis et al, 2004). Therefore we used sodium arsenite in all experiments for its convenience, ease of use, and identical structure of ATO and sodium arsenite in solution.…”
Section: Cell Culture and Specialty Chemicalsmentioning
confidence: 99%
“…Arsenic trioxide, which is As 2 O 3 in the solid, anhydrous form and As (OH) 3 in solution at physiological pH [4], is used clinically as a chemotherapeutic drug for treatment of acute promyelocytic leukemia [5]. Although epidemiological studies demonstrated that arsenic exposure is associated with a high frequency of circulatory and neurological problems [2,6,7], how arsenic causes non-cancer-related diseases is far from clear.…”
Section: Introductionmentioning
confidence: 99%
“…Most plants appear to have high levels of endogenous arsenate reductase activity, which reduces Ͼ95% of the arsenate they take up to arsenite (5,8). Arsenite, which at neutral pH contains arsenic in the trivalent oxidation state [As(III)], and probably as the acid HAsO 3 2Ϫ , is highly reactive and readily forms As(III)-thiol complexes (9). It appears that in most plants, arsenite is sequestered in roots, preventing it from moving up into stems, leaves, and reproductive organs.…”
mentioning
confidence: 99%